Intercostal Nerve Cryoablation for Postoperative Pain Control After the Nuss Procedure in Children: A Systematic Review and Meta-Analysis - Marques, Diogo; Vieira, Rafael; Fragoso, Ana; Tuna, Tiago (European Journal of Pediatric Surgery, 2025)
Nuss procedure is the standard technique for pectus excavatum repair. Despite its minimally invasive nature, this procedure is associated with significant postoperative pain and high opioid consumption. Intercostal nerve cryoablation (INC) has emerged as an adjunct to multimodal analgesia (MMA) to improve pain control, reduce opioid use, and shorten length of stay (LOS). This systematic review aims to assess INC outcomes following the Nuss procedure in pediatric patients.A systematic search was conducted in PubMed, Web of Science, Scopus, and Cochrane Library databases through December 2024. Studies comparing INC with standard MMA, with or without thoracic epidural, in pediatric patients undergoing the Nuss procedure were included. The primary outcome was LOS, and the secondary outcomes were opioid consumption, postoperative pain, complications, operative time, and hospitalization costs. Risk of bias was determined using the National Institutes of Health assessment tool. Meta-analysis was performed using R software.Eleven studies met the inclusion criteria, comprising 922 patients (476 INC and 446 control). INC significantly reduced LOS (−2.2 days; 95% CI: −2.8 to −1.8) at the expense of increased operating room time (+23 minutes; 95% CI: 10–39). Qualitative analysis showed reduced opioid use and comparable pain scores and complication rates with INC, while its impact on costs was conflicting.INC reduces LOS and opioid use in pediatric patients undergoing the Nuss procedure without increasing complications. Further studies are needed to assess long-term safety and cost-effectiveness.
Keywords: cryoablation; pectus excavatum; Nuss procedure